Benefits of Floating Wetlands beyond water pollution control: : A new perspective for Urban Landscape - Mendes, Maria Estela Ribeiro; Pina, Silvia A. Mikami G. (National Journal of City Management, 2026)
Objective – To synthesize and analyze existing knowledge on the implementation of Floating Treatment Wetlands (FTWs) in water bodies, identifying contributions beyond water quality improvement and their potential as an urban landscape strategy to promote Nature’s Contributions to People (NCP). Methodology – A Systematic Literature Review (SLR) to identify the main aspects addressed on the topic in scientific publications since 2012, a timeframe that explores the theoretical framework of Nature-based Solutions (NbS), an important reference for the multifunctional perspective of FTWs. Originality/Relevance – Urban water bodies are in increasing decline, not only due to the degradation of water quality but also their invisibility in the population’s daily life, a scenario that reveals the profound disconnection between people and nature. Thus, FTWs can be a strategy for the use and appropriation of spaces near water, promoting cultural and ecological values. Results – The implementation of FTWs promotes socio-environmental benefits across all NCP categories (material, non-material, and regulating contributions), confirming their potential for comprehensive integration into urban planning as an NbS, and not merely as a water treatment method. Theoretical/Methodological Contributions – A new perspective on the benefits of implementing FTWs in the urban landscape, valuing their multifunctionality, including the suggestion of a nomenclature that reflects such breadth: Floating Ecosystems (FE). Social and Environmental Contributions – Emphasis on the socio-environmental value of FTWs in improving the quality of life, the requalification of urban space, and ecological functions in the promotion of NCP.